The demand for assisting technologies in nursing and medical care: some comments. (1st January 2012) - Fachinger, Uwe
The aim of the paper is to systematise fundamental economic aspects to explain the demand of private households for assisting technologies. The paper shows that previous discussions examined only parts of the problem and ignored relevant determinants. Therefore, some explanation is given for the low development of the market for assisting technologies. Summary results of this study may lead to the conclusion that the demand is low because: willingness to pay is rather small for assisting technologies all necessities are included in the benefits of the statutory healthcare and long-term care insurance system products may have the status of luxuries. However, attempts to answer the question why the demand for assisting technologies is low and why still no market has been developed leads to the conclusion that explanations have to take into account additional factors such as affinity for technology and the willingness to pay.